Cigarette smoking causes a worse long‐term outcome in persistent atrial fibrillation following catheter ablation. (1st March 2018) - Cheng, Wen‐Han; Lo, Li‐Wei; Lin, Yenn‐Jiang; Chang, Shih‐Lin; Hu, Yu‐Feng; Hung, Yuan; Chung, Fa‐Po; Chang, Ting‐Yung; Huang, Ting‐Chung; Yamada, Shinya; Salim, Simon; Te, Abigail Louise D.; et al.
Abstract: Introduction: Cigarette smoking contributes to the development of atrial fibrosis via nicotine. The impact of smoking on ablation results in persistent atrial fibrillation (AF) is unknown. We aimed to investigate the triggers and long‐term outcome between smokers and nonsmokers in the patients with persistent AF after catheter ablation. Methods: This study included 201 (177 males, 53 ± 10 years old) patients who received index catheter ablation, including pulmonary vein isolation (PVI) and complex fractionated atrial electrograms (CFAEs) ablation for persistent AF, retrospectively. Electrophysiological characteristics at the index procedure and long‐term outcome were investigated to determine the differences between smokers and nonsmokers. Results: Baseline characteristics were similar between two groups. Pulmonary vein (PV) triggers were found in all patients in the two groups. There was a higher incidence of nonpulmonary vein (NPV) triggers in smokers than in nonsmokers (61% vs. 31%, P < 0.05). There were no differences of the long‐term ablation outcomes between smokers and nonsmokers in Kaplan–Meier analysis. Smokers with PV plus right atrial NPV (RA‐NPV) triggers had a higher incidence of recurrence (log‐rank P < 0.05) than those without RA‐NPV triggers, but not in nonsmokers, after a mean follow‐up of 31 ± 25 months. Conclusions: Smoking increases the incidence of NPV triggers in patients with persistent AF. Smokers who have RA‐NPV triggers during index procedure do have a worse outcome after catheter ablation, indicating the harmful effects of nicotine to right atrium.